Hypertension among South African children in disadvantaged areas and associations with physical activity, fitness, and cardiovascular risk markers: A cross-sectional study. Issue 21 (2nd November 2021) - Joubert, Nandi; Walter, Cheryl; du Randt, Rosa; Aerts, Ann; Adams, Larissa; Degen, Jan; Gall, Stefanie; Müller, Ivan; Nienaber, Madeleine; Nqweniso, Siphesihle; des Rosiers, Sarah; Seelig, Harald; et al.
ABSTRACT: Childhood hypertension drives hypertension in later life; hence, assessing blood pressure in children is an important measure to determine current and future cardiovascular health. There is, however, a paucity of childhood blood pressure data, particularly for sub-Saharan Africa. This study explores blood pressure and associations with age, sex, socioeconomic status, physical activity, fitness, and cardiovascular risk markers. In the 'Disease, Activity and Schoolchildren's Health' (DASH) study, a cross-sectional analysis was conducted in disadvantaged neighbourhoods in the Eastern Cape province of South Africa. Assessments included blood pressure, accelerometer-measured physical activity, physical fitness, and cardiovascular risk markers. The study consisted of 785 children (383 boys, 402 girls, M = 12.4±0.9 years). Overall, 18% of the children were classified as hypertensive, while 20% were either overweight/obese, and almost four out of ten children did not meet global daily physical activity recommendations. Hypertensive children were more likely to be overweight/obese, χ 2 (2, 785) = 14.42, p < 0.01, but only if they did not meet physical activity recommendations, χ 2 (2, 295) = 11.93, p < 0.01. Considering the moderating effect which sufficient activity has on the relationship between hypertension and body weight, more emphasis should be placed on early primary health intervention and education strategies.